Effects of long-term Doppler ultrasound exposure on cochlea and cochlear nucleus in prenatal period in an experimental model. (12th December 2022) - Celiker, Metin; Beyazal Celiker, Fatma; Tumkaya, Levent; Oghan, Fatih; Ozgur, Abdulkadir; Mercantepe, Tolga; Terzi, Suat; Beyazal, Mehmet; Turan, Arzu; Cinar, Seda; Zengin, Ertan; Demir, Emine; et al.
Abstract: Background: New generation Doppler ultrasonography (DUSG) application effects on cochlea and cochlear nucleus (CN) are unclear. We aimed to investigate the effects of new generation DUSG application at different frequencies in prenatal period on cochlea and CN in rats. Objective: Twenty-four pregnant female rats were divided into three groups ( n = 8). Group 1 was the control group and was not subjected to any treatment. Group 2 was determined as the USG every day (USGED) treatment group. Group 2 has received DUSG application every day from the 4th to 18th day (20 min/15 per day). Group 3 has received DUSG application as "2 days/one dose as every other day application" (USG2D1) from the 4th to 18th day (20 min/8 every other day). Twenty-four female rats were sacrificed in 21 days. Also, 24 pups were sacrificed after two days. First day after born, the cochlear activities of the right ears of all pups were examined using DPOAEs. Second day, neural tissues from CN were evaluated histopathologically and immunohistochemically. Results: There was no any statistical difference between the groups in respect of histopathologically. USGED group showed mild caspase-3 positive neurons and glial cells. However, there was no significant difference between the USGED and other groups ( p >.05). Similarly, the rats applied with USG2D1 had mild caspase-3 expression, but no significant difference between the USG2D1 and other groups ( p >.05). Differences in DPOAE amplitudes, and therefore in cochlear activity, between the groups were revealed. The decrease in cochlear activity between the groups involved frequencies at 2, 8, 16, and 32 kHz ( p <.05). Conclusions: Multiple administration of new generation DUSG to pregnant rats has not shown harmful effects on the cochlear neural tissue. High frequencies are more sensitive in cochlea to apply DUSG.